Internet Of Things Technology In Designing School Bell System - Amin, Muhammad; Sarif, Muhammad Irfan; Zuriansyah, Alvin (Bahasa Indonesia, 2024)
The application of Internet of Things (IoT) technology in school bell systems presents an automated, efficient, and integrated solution for managing bell schedules in real-time. The system is designed using IoT devices such as microcontrollers (Arduino or ESP32), wireless communication modules, and cloud platforms for data storage. Users can manage the bell schedule through a web- or app-based interface, enabling remote access and control. In addition, integration with sensors and smart devices allows the system to support operational flexibility, such as schedule adjustments based on specific conditions. This design offers operational efficiency, ease of management, as well as the ability to increase productivity in school environments through IoT technology automation.